Shifting sensitivity of septoria tritici blotch compromises field performance and yield of main fungicides in Europe - Jørgensen, Lise Nistrup; Matzen, Niels; Heick, Thies Marten; O’Driscoll, Aoife; Clark, Bill; Waite, Katherine; Blake, Jonathan; Glazek, Mariola; Maumene, Claude; Couleaud, Gilles; Rodemann, Bernd; Weigand, Stephan; et al. (Frontiers in Plant Science, 2022)
Septoria tritici blotch (STB; Zymoseptoria tritici) is a severe leaf disease on wheat in Northern Europe. Fungicide resistance in the populations of Z. tritici is increasingly challenging future control options. Twenty-five field trials were carried out in nine countries across Europe from 2019 to 2021 to investigate the efficacy of specific DMI and SDHI fungicides against STB. During the test period, two single DMIs (prothioconazole and mefentrifluconazole) and four different SDHIs (fluxapyroxad, bixafen, benzovindiflupyr and fluopyram) along with different co-formulations of DMIs and SDHIs applied at flag leaf emergence were tested. Across all countries, significant differences in azole performances against STB were seen; prothioconazole was outperformed in all countries by mefentrifluconazole. The effects also varied substantially between the SDHIs, with fluxapyroxad providing the best efficacy overall, while the performance of fluopyram was inferior to other SDHIs. In Ireland and the UK, the efficacy of SDHIs was significantly lower compared with results from continental Europe. This reduction in performances from both DMIs and SDHIs was reflected in yield responses and also linked to decreased sensitivity of Z. tritici isolates measured as EC50 values. A clear and significant gradient in EC50 values was seen across Europe. The lower sensitivity to SDHIs in Ireland and the UK was coincident with the prevalence of SDH-C-alterations T79N, N86S, and sporadically of H152R. The isolates' sensitivity to SDHIs showed a clear cross-resistance between fluxapyroxad, bixafen, benzovindiflupyr and fluopyram, although the links with the latter were less apparent. Co-formulations of DMIs + SDHIs performed well in all trials conducted in 2021. Only minor differences were seen between fluxapyroxad + mefentrifluconazole and bixafen + fluopyram + prothioconazole; the combination of benzovindiflupyr + prothioconazole gave an inferior performance at some sites. Fenpicoxamid performed in line with the most effective co-formulations. This investigation shows a clear link between reduced field efficacy by solo SDHIs as a result of increasing problems with sensitivity shifting and the selection of several SDH-C mutations. The presented data stress the need to practice anti-resistance strategies to delay further erosion of fungicide efficacy.